Dentoalveolar trauma as a consequence of traffic accidents in Bucaramanga and its metropolitan area (2019)
Introduction: Dentoalveolar trauma includes all injuries that involve dental structures, alveolar bone, periodontium and surrounding soft tissues. Currently, the frequency of dentoalveolar trauma due to traffic accidents has been identified as a public health problem. Objective: Determine the frequency of dentoalveolar trauma caused by traffic accidents in Bucaramanga and the metropolitan area between 2010 and 2015. Materials and methods: a retrospective descriptive study was designed, in which expert reports, performed by the National Institute of Legal Medicine and Forensic Sciences - Regional Nooriente Bucaramanga in the period 2010-2015, were obtained. This information was drawn from the information systems SICLICO and SIAVACSIVELCE. Results: The frequency of dentoalveolar trauma caused by traffic accidents was 0.82%, where the masculine gender showing a greater predisposition. 45.45% of all dentoalveolar trauma caused by traffic accidents was found to have been suffered by the group aged between 16-30 years old. In the study population, 17.6% received soft tissue injuries and 13.9% received enamel fracture (with the most compromised dental group being the upper central incisors). With regards to the type of transport involved in the accidents, 74.2% of the cases were motorcyclists with the driver being affected most often (in 51.5% of the events). Conclusions: The dentoalveolar trauma caused by traffic accidents affected structures within the oral cavity such as soft tissues and hard tissues. The dental group most affected was that of the upper central incisors, and motorcycles were the automotive medium most involved in these events.